The Humanistic Burden of Small Cell Lung Cancer (SCLC): A Systematic Review of Health-Related Quality of Life (HRQoL) Literature - Bennett, Bryan M.; Wells, Jane R.; Panter, Charlotte; Yuan, Yong; Penrod, John R. (Frontiers in Pharmacology, 2017)
BACKGROUND: Little is known about the humanistic burden of small cell lung cancer (SCLC), specifically the impact on health-related quality of life (HRQoL). The aim of this systematic literature review was to explore the impact of SCLC on HRQoL and the patient reported outcomes (PROs) used to capture this impact. METHODS: We conducted a systematic search of Medline®, Embase, and PsycINFO, oncology organisation websites and conference proceedings within the past ten years. Articles reporting HRQoL outcomes of SCLC patients were selected. RESULTS: Twenty-seven eligible publications were identified. Global or overall impact on HRQoL (n=21) was reported most often, with considerably fewer reporting individual domains that comprise HRQoL. Results indicated that HRQoL was negatively impacted in SCLC patients in comparison to the normal population in most domains. Overall, the domains measuring physical functioning and activities of daily living were most impacted. However, results on cognitive and emotional functioning were inconclusive. The impact on HRQoL may be least in both limited disease and extensive disease (ED) SCLC patients who have responded to treatment, and greatest in ED patients who were treatment naïve. The most frequently used PRO’s were the EORTC QLQ-C30 core cancer instruments, the lung cancer specific module the EORTC QLQ-LC13, LCSS and EQ-5D. CONCLUSION: There exists a paucity of reporting on SCLC HRQoL outcomes. This extends to the reporting of domain level scores and by patient sub-group. Greater reporting at a granular level is recommended to allow for more robust conclusions to be made.